Understanding new media - Siapera, Eugenia, ....- (Los Angeles : SAGE, 2018)
The new media landscape touches every aspect of our social, political and cultural lives. It is more important than ever, therefore, that we are able to understand and explain the complexity of our digital world. Understanding New Media gives students the tools and the knowledge they need to make sense of the relationship between technologies, media and society. This best-selling student introduction: Makes complex ideas accessible, clearly explaining the key thinkers, theories and research students need to understandBrings theory to life with a range of new case studies, from selfies or trolling, to the app economy and algorithms in social mediaGets students started on projects and essays with guided research activities, showing them how to successfully put learning into practiceProvides guided further reading, helping students to navigate the literature and extend their studies beyond the chapter Understanding New Media remains the perfect guide to the past, present and future of the new media world. It is a vital resource for students across media and communication studies and sociology, and anyone exploring new media, social media or digital media.
Previous edition: 2012.
Includes bibliographical references and index.
Keywords: Digital communications -- Social aspects; Digital media -- Social aspects; Information society